1999
DOI: 10.1116/1.590852
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy of oxidative coupling reactions of phenols with FeCl3 in the solid state

Abstract: Potential dependent change in local structure of ferrocenyl-terminated molecular islands by electrochemical frequency modulation atomic force microscopyThe solid-solid chemical reactions of phenols or ketones, such as ␤-naphthol ͑1͒ or anthron ͑2͒, with FeCl 3 •6H 2 O by ultraviolet irradiation give coupling dimeric products. The mechanisms are studied using atomic force microscopy ͑AFM͒ and known crystal packing data. AFM reveals that the crystal face ͑100͒ of 2 or ͑001͒ of 1 exhibits stumpy protrusions all o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Recently, it has been applied to the submicroscopic investigation of chemical reactions on crystal solids. 1,2 These studies have revealed new perspectives in the realm of gas-solid reactions, [3][4][5][6][7] solid-solid reactions, [8][9][10][11] and crystal photolyses. [12][13][14][15][16][17][18][19] AFM measurements on single-crystal sur-faces reveal phase rebuildings with well-directed long-range molecular transports.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been applied to the submicroscopic investigation of chemical reactions on crystal solids. 1,2 These studies have revealed new perspectives in the realm of gas-solid reactions, [3][4][5][6][7] solid-solid reactions, [8][9][10][11] and crystal photolyses. [12][13][14][15][16][17][18][19] AFM measurements on single-crystal sur-faces reveal phase rebuildings with well-directed long-range molecular transports.…”
Section: Introductionmentioning
confidence: 99%